The Weight Evaluation of Intellectual Capital’s Key Factors Upon Financial Performance of the Listed IC Design Houses in Taiwan - Lee, Yu-Je; Chang , Chung-Ming; Wu, Mei-Fen (Asian Journal of Empirical Research, 2014)
The main purpose of this study is to evaluate the weight value of intellectual capital’s key factors that affect financial performance of the listed IC Design Houses in Taiwan. The research subjects are five typical listed Taiwan IC design houses. This paper adopts Analytic Network Process (ANP) to analyze the relevance of each criterion, and to identify the important factors of each criterion and the priority ranking of their weights. Research findings show that, in the intellectual capital sub-dimension affecting the financial performance of the listed IC design houses in Taiwan, the weights from both the academic scholars’ perspective and industry operators’ perspective are over 0.1. This fact shows that both scholars and business operators believe that customer capital, process capital, human resource capital and innovation capital are the important indicators that affect financial performance. Although the weight values of business operators’ perspectives on the above-mentioned four factors are different from those of the scholars’, this difference arises because scholars take on a theoretical viewpoint, believing that innovation capital impacts financial performance the most; while business operators take on a more practical view, believing that customer capital impacts financial performance the most.